Gingivitis resolution followed by optical coherence tomography and fluorescence imaging: A case study - Le, Nhan; Cheng, Harrison; Subhash, Hrebesh; Kilpatrick‐Liverman, LaTonya; Wang, Ruikang K. (Journal of biophotonics, 2021)
Gingivitis is highly prevalent in adults, and if left untreated, can progress to periodontitis. In this article, we present an interesting case study where the resolution of gingivitis was followed over a period of 10 days using optical coherence tomography (OCT) and light‐induced autofluorescence (LIAF). We demonstrate that OCT and its functional angiography can distinctively capture the changes during the resolution of gingivitis; while LIAF can detect red‐fluorescent signals associated with mature plaque present at the inflamed site. The acute inflammatory region showed evidence of angiogenesis based on the quantification of vessel density and number; while no angiogenesis was detected within the less inflamed region. Gingival thickness showed a reduction of 140 ± 26 μm on average, measured between the peak gingivitis event and the period wherein the inflammation was resolved. Vessels in the angiogenesis site was found to reduce exponentially. The mildly inflamed site showed a decreasing trend in the vessel size, which however was within the error of the measurement. OCT angiography provides detailed information of microvascular involvement during a reversible gingivitis over a time course from Day 0 to Day 11 at which time the subject was scheduled for teeth cleaning. Shown are the vessel‐depth encoded color vascular maps for better 3D appreciation.